1999
DOI: 10.1074/jbc.274.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Nix and Nip3 Form a Subfamily of Pro-apoptotic Mitochondrial Proteins

Abstract: We have identified Nix, a homolog of the E1B 19K/Bcl-2 binding and pro-apoptotic protein Nip3. Human and murine Nix have a 56 and 53% amino acid identity to human and murine Nip3, respectively. The carboxyl terminus of Nix, including a transmembrane domain, is highly homologous to Nip3 but it bears a longer and distinct asparagine/proline-rich N terminus. Human Nip3 maps to chromosome 14q11.2-q12, whereas Nix/BNip3L was found on 8q21. Nix encodes a 23.8-kDa protein but it is expressed as a 48-kDa protein, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
223
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(229 citation statements)
references
References 18 publications
(29 reference statements)
3
223
1
2
Order By: Relevance
“…The protein contains a BH3 domain that induces apoptosis (Yasuda et al, 1998) and a C-terminal transmembrane domain that is required for both its mitochondrial localisation and its proapoptotic activity (Chen et al, 1997(Chen et al, , 1999Yasuda et al, 1998); it has been suggested that BNIP3 mediates a necrosis-like cell death by causing mitochondrial dysfunction (Harris, 2002). Hypoxia induces expression of a group of genes, among which is the transcriptional regulator HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…The protein contains a BH3 domain that induces apoptosis (Yasuda et al, 1998) and a C-terminal transmembrane domain that is required for both its mitochondrial localisation and its proapoptotic activity (Chen et al, 1997(Chen et al, , 1999Yasuda et al, 1998); it has been suggested that BNIP3 mediates a necrosis-like cell death by causing mitochondrial dysfunction (Harris, 2002). Hypoxia induces expression of a group of genes, among which is the transcriptional regulator HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these BH3-only factors localize to and (by activating BAX and BAK) permeabilize mitochondrial outer membranes, which activates the intrinsic apoptosis signaling pathway (Chen et al, 1999). Preventing mitochondrial localization of either BNIP3 or NIX/BNIP3L by mutational deletion of C-terminal mitochondrial targeting sequences creates dominant inhibitory proteins (Regula et al, 2002;Yussman et al, 2002).…”
Section: Cardiomyocyte Apoptosis and Bcl2 Proteins In Myocardial Diseasementioning
confidence: 99%
“…Preventing mitochondrial localization of either BNIP3 or NIX/BNIP3L by mutational deletion of C-terminal mitochondrial targeting sequences creates dominant inhibitory proteins (Regula et al, 2002;Yussman et al, 2002). Both proteins are also subject to rapid degradation by the ubiquitin-proteosome pathway (Chen et al, 1999;Cizeau et al, 2000), accounting for barely detectable levels observed in the unstressed myocardium. Importantly, there appears to be no essential physiological or developmental function for either NIX/BNIP3L or BNIP3 in the heart, as cardiac structure and function are normal in the respective cardiac-specific and germ-line gene knockout mouse models (Diwan et al, 2007b(Diwan et al, , 2008b.…”
Section: Cardiomyocyte Apoptosis and Bcl2 Proteins In Myocardial Diseasementioning
confidence: 99%
“…Paradoxically, expression of the antiapoptotic regulator, IAP-A (Goyal, 2001), decreased more than 50%, whereas expression of NIX (Chen et al, 1999), a pro-apoptotic Bcl-2 family member, increased approximately twofold in differentiating C2C12 cells (Table 2). These observations suggest that the survival of differentiating C2C12 cells and differentiated myotubes may depend on the balance of pro-and anti-apoptotic activities at the cellular level.…”
Section: Coordinate Regulation Of Cell Cycle Withdrawal and Apoptosismentioning
confidence: 99%